English unlimited - Doff, Adrian (Cambridge University Press, 2011)
Through challenging, contemporary topics and activities, and a focus on intercultural competence as a 'fifth skill', this international coursebook helps Advanced learners become more effective communicators. Teaching natural, dependable language, with CEF goals at its core, it brings real life into the classroom and gives learners the skills and strategies to communicate confidently outside it. Explore sections provide the extra ingredients for enhancing communicative ability, further developing speaking and writing skills through authentic texts. The e-Portfolio DVD-ROM enables learners to create a 'can-do' record of their work and progress. It also includes reference tools, interactive wordlists, and a vocabulary trainer